The court as last resort. Victim-sensitive, community-based responses to crime - Wright, Martin (The British journal of criminology, 2002)
This paper considers the claimed benefits for victims in restorative justice processes. The author argues that these objectives can best be achieved through a focus on three overlapping areas; the structure for the delivery of services, mediation practice and a focus on the arrangements for dealing with cases where mediation is not possible. Recent legislation and practice in the United Kingdom are examined to consider the extent to which such initiatives have improved (or not) the delivery of services to victims. Finally, an agenda is proposed for victim-sensitive justice that includes procedural changes, safeguards, and greater community involvement